2015
DOI: 10.1007/s11540-015-9298-0
|View full text |Cite
|
Sign up to set email alerts
|

Residue Mulch Effects on Potato Productivity and Irrigation and Nitrogen Economy in a Subtropical Environment

Abstract: Depleting water resources in many regions of the world and increasing fertilizer nitrogen (N) cost necessitate efficient resource use. This is crucial in shallow-rooted crops like potato due to a great probability of water and N loss. In Indian Punjab, autumn potato experiences high temperature at planting time that causes poor growth and tuber yield. Mulching with crop residues provides favorable soil hydrothermal conditions that may enhance yield and economize irrigation and N use. This study examined the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…In the present study, the soil water content in the top 0-20 cm of soil under IMP was significantly higher than that under FP on average, primarily as a consequence of straw mulching (Figure 3), which was consistent with the findings of Chang et al [36] and Deng et al [37] in the Loess Plateau of China and those of Singh et al [38] in a subtropical region of India. First, IMP decreased the soil temperature by reducing direct solar radiation owing to the straw mulching (Figure 2), thus reducing the evaporation of soil water.…”
Section: Integrated Management Practice Optimized Soil Temperature and Soil Water Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the soil water content in the top 0-20 cm of soil under IMP was significantly higher than that under FP on average, primarily as a consequence of straw mulching (Figure 3), which was consistent with the findings of Chang et al [36] and Deng et al [37] in the Loess Plateau of China and those of Singh et al [38] in a subtropical region of India. First, IMP decreased the soil temperature by reducing direct solar radiation owing to the straw mulching (Figure 2), thus reducing the evaporation of soil water.…”
Section: Integrated Management Practice Optimized Soil Temperature and Soil Water Contentsupporting
confidence: 92%
“…Crop straw mulching techniques have been widely used in arid and semi-arid regions to improve crop yields [38,46,52,53]. In a study conducted in a semi-arid region, Chang et al [36] showed that straw strip mulching increased the yields of potato by 22.3% on average compared with traditional practices (bare soil).…”
Section: Integrated Management Practice Promoted Soybean Growth and Yieldmentioning
confidence: 99%
“…Potato is a shallow‐rooted and cool‐season crop, and temperature is the key factor that affects the tuber bulking and the balance between the vine and tuber growth of potato plants (MacKerron et al., 1986; Zhang et al., 2017). Potato growth is optimum when mean air temperature is around 15–18°C during the cropping cycle (Singh, Singh, Arora, & Sekhon, 2015). Appropriate temperature is crucial to increasing potato yield and RBT (Li et al., 2018; WoLi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Organic mulch on potato crop is a technique that can reduce the erosion and loss of soil organic matter, NO 3 --N and available P, K, Ca and Mg by runoff, increasing the total and marketable tubers yields (Rees et al 2002). Mulching with organic residues decreases the soil thermal amplitude and soil water evaporation, thus increasing the N uptake and the efficiency of the N fertilization to enhance higher potato tuber yields (Singh et al 2015). Besides this buffer effect on the soil hydrothermal conditions, organic mulching also adds plant nutrients to the soil after decomposition, but also can immobilize N by microorganisms (Kader et al 2017) and, therefore, reduces the NO 3 --N leaching to the soil profile (Döring et al 2005).…”
Section: Abstract Resumomentioning
confidence: 99%